Tasks of management, outlooking from the needability of ensuring optimal resource use modes and key aspects of the management process - Savenko, V.; Palchik, S.; Malets, N.; Karim, A.; Anas, A. (Ways to Improve Construction Efficiency, 2019)
The task of finding an optimal control or control in general should be considered as not causing any problems, if there are no restrictions on the nature of the system movement. In general, there are two types of restrictions on the choice of control method. The limitations of the first type are the laws of nature themselves, according to which the movement of the controlled system occurs. In the mathematical formulation of the control problem, these constraints are usually represented by the algebraic, differential, or difference equations of the control object and are often called coupling equations.